Women Writers and Public Debate in 17th-Century Britain - Gray, C. author. aut Link
X, 263 p.
Keywords: This book reveals women writers' key role in constituting seventeenth-century public culture and, in doing so, offers a new reading of that culture as begun in intimate circles of private dialogue and extended along transnational networks of public debate.